Catalytic Fehling's Reaction: An Efficient Aerobic Oxidation of Aldehyde Catalyzed by Copper in Water - Liu, Mingxin; Li, Chao-Jun (Angewandte Chemie International Edition, 2016)
The first example of homogeneous copper‐catalyzed aerobic oxidation of aldehydes is reported. This method utilizes atmospheric oxygen as the sole oxidant, proceeds under extremely mild aqueous conditions, and covers a wide range of various functionalized aldehydes. Chromatography is generally not necessary for product purification. Without ‘Fehl ’: The first example of homogeneous copper‐catalyzed aerobic oxidation of aldehydes is reported. This method utilizes atmospheric oxygen as the sole oxidant, proceeds under extremely mild aqueous conditions, and covers a wide range of various functionalized aldehydes. Chromatography is generally not necessary for product purification.